Clinical features and pathogen distributions of microbiological-based protracted bacterial bronchitis in children of different ages in Northeast China - Chen, Ning; Zhang, Han; Feng, Yong (Frontiers in Pediatrics, 2023)
Background: Protracted bacterial bronchitis (PBB) is often diagnosed clinically according to chronic wet cough, which can be resolved by appropriate antibiotics. Though rarely performed in PBB diagnosis, bacterial cultures by sputum or bronchoalveolar lavage (BAL) fluid can provide etiological features, which may be different in western countries and different areas of China. This study aimed to investigate the clinical and etiological features and outcomes in children of different ages with PBB in northeast China. Methods: We retrospectively analyzed children diagnosed with PBB by positive BAL fluid or sputum bacterial cultures between 2017 and 2021. Children were divided into three age groups: <1 year (infants), 1–5 years (younger children), and ≥6 years (older children). Clinical characteristics, chest radiographic findings, bronchoscopy findings, microbiological findings, treatment strategies, and outcomes were reviewed and compared among the age groups. Factors associated with remission during follow-up were examined using logistic regression. Results: A total of 45 children with PBB were included, consisting of 24 (53.3%) infants. The infants were often boys and had a shorter cough duration, a lower proportion of expectoration, a greater proportion of wheezing, and less bronchial wall thickening on high-resolution computed tomography compared to older children (P <0.05). No significant differences were found among the age groups regarding macroscopic findings, except for a higher proportion of tracheobronchial malacia in infants than in older children (P = 0.013). The most commonly cultured bacteria were Haemophilus influenzae (42.2%), followed by Streptococcus pneumoniae (22.2%) and Klebsiella pneumoniae (20.0%). Compared to older children, infants had a higher remission (P = 0.009) and relatively lower relapse rates (P = 0.059). Short duration of cough (OR=0.58, 95% CI: 0.34–0.99, P = 0.046) and absence of recurrent cephalosporins before diagnosis (OR=0.05, 95% CI: 0.00–0.73, P = 0.028) were associated with remission. Conclusions: Infants are more prone to PBB, with increased wheezing. Gram-negative bacilli infections are common in infants in northeast China. Older children with PBB should be carefully assessed, treated and followed up, particularly those with long duration of cough and poor response to antibiotic treatments.